Study Of PM2.5 Concentration At School Near Road Side In Penang - Ramli, Nur Amanina (Universiti Sains Malaysia, 2018)
The monitoring program monitored the relationship of indoor and outdoor concentrations of the fine particles (PM2.5). Four schools were selected in this study. The concentration of fine particulate matter was monitored at different classes with different floor level. PM2.5 concentrations were monitored in close proximity to a road side in order to determine whether traffic affect indoor concentration of PM2.5 at this location. Other existing possible sources around the monitoring location were also considered. PM2.5 concentrations were collected at Sekolah Kebangsaan Bayan Lepas, Sekolah Kebangsaan Tasek Gelugor, Sekolah Menengah Kebangsaan Mutiara Impian and Sekolah Kebangsaan Machang Bubok. The monitoring program was launched on January 16, 2018 and continued until March 13, 2018. The monitoring data at different floor level was taken intermittently with 15 minutes interval . E-sampler was positionedat the back of the classroom and E-bam was positioned at outside of the school near to the roadway. Meteorological information was collected using two instruments and traffic information was continuously collected via video camera at or near the monitoring site facing to the road. The data recorded using the specification monitor were analyzed using SPSS software to determine the relationship of the PM2.5 indoors and outdoors and its differences of the concentration at different floor level. The indoor/outdoor (I/O) ratio analysis were 0.74 and 0.76 at second floor level and third floor level of Sekolah Kebangsaan Bayan Lepas which shows the contribution from the outdoor sources toward the indoor concentration of PM2.5. In contrast, the other three schools show vice versa. Based on the apportionment analysis, the contribution of roadway sources are not really strong based on the result analysed using Pearson Correlation.